Atlas of gastrointestinal pathology : a pattern based approach to neoplastic biopsies /: a pattern based approach to neoplastic biopsies. (2018) - Arnold, Christina A; Lam-Himlin, Dora M; Montgomery, Elizabeth (Elizabeth A.), 1958-
No abstract available